Retrieving the True Masses of Gravitational Wave Sources - Xian Chen; Zhefeng Shen (Proceedings, 2019)
Gravitational waves (GWs) encode important information about the mass of the source. For binary black holes (BBHs), the templates that are used to retrieve the masses normally are developed under the assumption of a vacuum environment. However, theories suggest that some BBHs form in gas-rich environments. Here, we study the effect of hydrodynamic drag on the chirp signal of a stellar-mass BBH and the impact on the measurement of the mass. Based on theoretical arguments, we show that the waveform of a BBH in gas resembles that of a more massive BBH residing in vacuum. The effect is important for those GW sources in the band of space-borne detectors but negligible for those in ground-based ones. Furthermore, we carry out a matched-filtering search of the best fitting parameters. We find that the best-fit chirp mass could be significantly greater than the real mass when the gas effect is ignored. Our results have important implications for the future joint observation of BBHs using both ground- and space-based detectors.